Aronia berry polyphenols have matrix-dependent effects on the gut microbiota. (15th October 2021) - Liu, Xiaocao; Martin, Derek A.; Valdez, Jonathan C.; Sudakaran, Sailendharan; Rey, Federico; Bolling, Bradley W.
Highlights: Aronia berry polyphenols have matrix-dependent effects on gut microbiota in mice. Aronia berry non-extractable polyphenols are accessible to the gut microbiome. Aronia fiber increases carbohydrate fermentation in the gut of healthy mice. Abstract: The objective of this study was to determine the extent that the aronia berry matrix affects gut microbiota composition, fecal short chain fatty acids (SCFAs), and colonic anthocyanins in healthy mice. C57BL/6J mice were fed AIN-93 M control diet (C) or C with whole aronia berry (AB), aronia extract (AE), or polyphenol-depleted AB (D) at the expense of cornstarch. After one week of feeding, AB and D increased fecal anthocyanins more than AE. Diets differentially affected SCFA and microbiota. AB fecal SCFA was associated with increased metabolism of succinate and pyruvate to butyrate. D increased acetic acid production, was associated with increased abundance of predicted genes for fermentation of carbohydrates to acetyl-coA. AB and D also increased predicted abundance of microbial catechol metabolism pathway I relative to C, which was attributed to enrichment of Lachnospiraceae. Therefore, the berry matrix impacts how aronia polyphenols interact with the gut microbiota in healthy mice.